Penerapan Mesin Perajang Dan Penggoreng Kentang Semi Automatis Guna Mempercepat Proses Produksi Kentang Goreng Produk UMKM “Make - D” - Padang Yanuar; Ign. Gunawan Widodo; Atikah Ayu Janitra; Sri Harmanto; Ampala Khoryanton; Eni Safriana; Arif Pambekti; Eri Prihatmini (CV. Multi Kreasi Media, 2025)
UMKM Make-D is located in Dieng Kulon Tourism Village, one of the villages in Batur District, Banjarnegara Regency. Potato chips are a typical souvenir from this area, along with the increase in tourist visits in proportion to the demand for potato chips. The production process is still traditional, making it difficult for UMKM to meet customer demand. The goal of the mechanical engineering lecturer community service team is to implement a semi-automatic chopping and frying machine to help speed up the production process of quality fried shallots. The method in this community service begins with identifying partner problems, the next stage is to conduct a group discussion with the community service team to discuss problem solutions, the result of this community service is the application of appropriate technology for semi-automatic chopping and frying machines to improve the potato chip production process.